Dynamic systems : modeling and analysis - Vu, Hung V.; Esfandiari, Ramin S. (New York : McGraw-Hill, 1997)
A guide to modeling and analysis techniques, emphasising the fundamentals and including many thoroughly worked examples as well as frequent use of free body and effective force diagrams. Aimed at mechanical engineering students.
Includes bibliographical references (p. 612-613) and index.
oif 16/09/15
Loan
Keywords: Engineering -- Mathematical models; Systems engineering -- Mathematical models; Dynamics; System analysis